Kedudukan Aset Kripto sebagai Sarana Penyembunyian Hasil Tindak Pidana Pencucian Uang ( Studi Kasus Putusan Nomor 111/Pid.B/2022/PN Kbm jo. Putusan Nomor 97/Pid/2023/PT SMG) - Ananda Putri; Bintang Wicaksono Ajie (HUMANIORUM, 2026)
This research aims to analyze the legal position of cryptocurrency assets and their use as a means of concealing proceeds from money laundering offenses, using the Kebumen District Court Decision No. 111/Pid.B/2022/PN Kbm in conjunction with the Semarang High Court Decision No. 97/PID/2023/PT SMG as a case study. The research uses a normative juridical method, examining positive legal norms through library research, focusing on Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering, as well as regulations from Bappebti (and later OJK) regarding cryptocurrency assets. The research findings indicate that the court classified cryptocurrency assets as "property" under Articles 2 and 3 of Law No. 8 of 2010, as they have economic value and are transferable, making them valid objects for money laundering offenses. The actions of the defendant, Fitriyani alias Fitri Crypto, converting fraudulently obtained funds into cryptocurrency assets and transferring them through various digital wallets, were seen as a form of disguising the origin of the assets, fulfilling the elements of money laundering under Articles 3 and 4 of the law. This decision provides legal certainty that digital assets can be treated the same as conventional assets in criminal cases. However, the research also highlights ongoing technical challenges in the seizure and proof of ownership of digital assets due to the pseudonymous nature of cryptocurrency transactions